Researching of University Students Sport Consumption - Mahmut Elmas; Velittin Balcı (Türk Spor ve Egzersiz Dergisi)
The study determines the rank of consuming sport and sporting goods behavior of university students and presents ideas to develop this behaviour. Sport marketing and sport consuming litarature has been scanned in content of the research. The research has been applied by using a scale developed by Elmas et al. (2018) which consist three dimensions as event consuming, media consuming and sporting goods consuming. After verifiying the scales reliabilitys and validity, normal distrubituon checked and one sample t-test for bileteral variables, one way anova test for multi variables applied. The study’s scale has been applied by using random expample medhod on sophomore and further class students of university students in Ankara/Turkey to collect data. University students sport consuming status according to their demographic values are reported at end of the research. The scale has two parts, demographic informations as a first and sport consuming scale as second part. SPSS 20 has used to evaluate to collected data. It seems that male students consumes more sport than female students end of the research. Moreover according to results, while younger students attends sport related events more than older ones, students consumes more sporting goods who has middle income than high or low ones. Students who does any kind of sport or follows it consumes more sport in all three dimentions.